2000
DOI: 10.1001/jama.283.15.1983
|View full text |Cite
|
Sign up to set email alerts
|

Enduring Effects of Nurse Home Visitation on Maternal Life Course

Abstract: We found enduring effects of a home visitation program on the lives of black women living in an urban setting. While these results were smaller in magnitude than those achieved in a previous trial with white women living in a semirural setting, the direction of the effects was consistent across the 2 studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 27 publications
4
119
0
5
Order By: Relevance
“…We believe that nurse-visited low-resource mothers chose to focus their resources on the care and protection of their children, and this explains why they were particularly successful, compared with their control-group counterparts, in managing the care of their firstborn children, as reflected in their children's having fewer injuries through age 2 and better cognition, arithmetic achievement, adjustment at age 6, and academic achievement in grades 1 to 3. 7,8,11,12 It is possible that the reduction in use of AFDC/TANF and food stamps observed during the 9-year period after birth of the first child for the entire sample may be explained at least in part by the nurse-visited women's increased involvement with the first child's biological father and the stability of partnered relationships, given that their partners were frequently employed and most likely brought additional financial resources to the household. In 1996, the US welfare reform act went into effect, 31 limiting women's lifetime use of public assistance (TANF).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that nurse-visited low-resource mothers chose to focus their resources on the care and protection of their children, and this explains why they were particularly successful, compared with their control-group counterparts, in managing the care of their firstborn children, as reflected in their children's having fewer injuries through age 2 and better cognition, arithmetic achievement, adjustment at age 6, and academic achievement in grades 1 to 3. 7,8,11,12 It is possible that the reduction in use of AFDC/TANF and food stamps observed during the 9-year period after birth of the first child for the entire sample may be explained at least in part by the nurse-visited women's increased involvement with the first child's biological father and the stability of partnered relationships, given that their partners were frequently employed and most likely brought additional financial resources to the household. In 1996, the US welfare reform act went into effect, 31 limiting women's lifetime use of public assistance (TANF).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed children's school records in grades 1 to 3 and obtained teachers' (primarily thirdgrade) reports of children's classroom behavior. The details of basic study design and its implementation have been reported previously 11,12 and are summarized here. Table 1 provides the numbers of eligible patients who were (1) invited to participate, (2) randomly assigned, and (3) evaluated at each follow-up assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our measurement approach was based on the work of Kitzman et al 15 In brief, participating women were interviewed by trained interviewers at the time of enrollment and when the child reached 12 months of age. The enrollment interview collected data on demographic, 5 obstetrical, and medical histories, and data on health-related behaviors (eg, smoking, alcohol use), stress, selfefficacy, and social support.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Use of human services was measured by asking mothers about their current receipt of WIC and Aid to Families With Dependent Children (AFDC), an approach found comparable to secondary data collection. 15 …”
Section: Study Design and Data Collectionmentioning
confidence: 99%